Case report: a fatal case of Aspergillus felis infection in an immunocompetent host. Issue 11 (21st November 2022) - Parkes-Smith, Jill; Bauer, Michelle J.; Bergh, Haakon; Eidan, Anthony; Forde, Brian M.; Hilton, John; Kidd, Timothy J.; Schmidt, Campbell; Stewart, Adam G.; Harris, Patrick N. A.
Abstract : We report a fatal case of Aspergillus felis invasive rhinosinusitis with secondary cerebral abscesses in an immunocompetent host despite aggressive surgical debridement and combination antifungals. Whilst this organism is known to cause fatalities in cats, only a few cases in humans have been documented, all of which had significant immunosuppression. This is the first human death due to A. felis described in an immunocompetent host.